The Protestation Protested, 1641 And 1642 - Cressy, David (The historical journal, 2002)
Parliament's Protestation of May 1641 pledged subscribers to defend the protestant doctrine of the Church of England against all popery and popish innovations, while upholding the honour of the king, the privileges of parliament, and the liberties of the subject. The following twelve months saw contentious debate about the ambiguity of these phrases and the conflicting obligations they entailed. Leaders of the political nation subscribed the Protestation voluntarily in the summer of 1641, emulated in some places by ordinary parishioners. In the more polarized political circumstances of early 1642, parliament ordered the Protestation to be taken nationwide by all men aged eighteen and above. Women, too, occasionally subscribed. This article traces the tendering and reception of the Protestation on both occasions, and examines some of its local consequences. The circulation of the Protestation significantly widened the arena for political and religious involvement in the opening stages of the English revolution.